Managing activities : a competence approach to supervisory management - Collins, Michael.; Green, George.; Candy, Anita.; . (Blackwell Business, 1998)
Seeting operations in context. The operations process. Planning. Organizing and implementation. Control. Communicating with the customer. Managing materials. Managing the working environment. Personal competences.